MIT APP INVERTOR PADA APLIKASI SCORE BOARD UNTUK PERTANDINGAN OLAHRAGA BERBASIS ANDROID - Muhammad Najib Dwi Satria; Fajar Saputra; Donaya Pasha (Jurnal Teknoinfo, 2020)
Technological developments change various sectors of the world's life that are present in order to facilitate human work in carrying out their daily tasks. An example is an android smartphone that comes with various features as needed. The presence of a competition system that utilizes technology will certainly facilitate the assessment of referees to determine the winner. In addition, it makes it easier for the committee to manage scores by remote control using a smartphone in real time. The match system between branches is certainly different, both in terms of scoring and match time. Therefore the authors build an Android-based application that is integrated with the score board that is used to facilitate the referee to determine the match scores in several sports. Because it is known that each sport has different regulations regarding the scoring system and its time. The results of this study are to produce an application score board using the P10 LED matrix that can be controlled via an Android smartphone. The score board application is made capable of being used in several sports such as futsal, basketball, volleyball and badminton..